Kesesuaian dan Daya Dukung Ekowisata di Kawasan Mangrove Tambatan Hati Pelangi Kecamatan Tilamuta Kabupaten Boalemo Provinsi Gorontalo - Novita Wantu; Sri Nuryatin Hamzah; Sitti Nursinar (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2022)
ABSTRACTThe study aims to determine the suitability and carrying capacity of mangrove ecotourismin the Tambatan Hati Pelangi area Pentadu Timur Village, Tilamuta District, Boalemo Regency Gorontalo Province. The research was conducted from December 2021 to January 2022 using quadrant method with a size of 10×10 m. The data was analyzed using the Tourism Suitability Index (TSI) analysis matrix and the carrying capacity of the Area (CCA) assessment to determine the maximum number of visitors that can be accommodated. The criteria for tourism suitability observed were mangrove thickness, mangrove density, mangrove species, tides and biota objects. The results showed the TSI on each line transect was in a suitable category with TSI value 2.02-2.27. The area that can be used for tourism is 19,320 m2. The Tambatan Hati Pelangi mangrove area in East Pentadu Village as a whole is included in the appropriate category for mangrove ecotourism with a visitor capacity of 1546 people/day.Keywords: Mangrove ecotourism, suitability, carrying capacity, Pentadu Timur, GorontaloABSTRAKPenelitian ini bertujuan untuk mengetahui kesesuaian dan daya dukung ekowisata mangrove di kawasan Tambatan Hati Pelangi Desa Pentadu Timur Kecamatan Tilamuta Kabupaten Boalemo Provinsi Gorontalo. Penelitian ini dilaksanakan pada bulan Desember 2021 sampai Januari 2022, menggunakan metode kuadran dengan ukuran 10×10 m. Data dianalisis dengan menggunakan matriks analisis Indeks Kesesuaian Wisata (IKW) dan penilaian Daya Dukung Kawasan (DDK) untuk menentukan jumlah maksimum pengunjung yang dapat ditampung. Kriteria kesesuaian wisata yang diamati adalah ketebalan mangrove, kerapatan mangrove, jenis mangrove, pasang surut dan objek biota. Hasil penelitian menunjukkan IKW pada masing-masing transek garis berada pada kategori sesuai dengan nilai IKW 2,02-2,27. Luas area yang dapat dimanfaatkan untuk kawasan wisata 19.320 m2. Kawasan mangrove Tambatan Hati Pelangi Desa Pentadu Timur secara keseluruhan termasuk dalam kategori sesuai untuk ekowisata mangrove dengan kapasitas daya tampung pengunjung 1546 orang/hari.Kata Kunci: ekowisata mangrove, kesesuaian, daya dukung, Pentadu Timur, Gorontalo